Beyond biodiversity: does “Farming with Alternative Pollinators” also boost farmers’ income in wheat (Triticum aestivum L.) fields? a case study in Morocco - Bencharki, Youssef; Michez, Denis; Smaili, Moulay Chrif; Ihsane, Oumayma; Aw-Hassan, Aden; Ssymank, Axel; Rasmont, Pierre; Christmann, Stefanie (Frontiers in Ecology and Evolution, 2025)
The importance of flower visitors for ecosystem resilience and crop production underscores the need to address the current decline of flower visitors worldwide. Farming Alternative Pollinators (FAP), economic and ecological benefits of fields hosting various marketable habitat enhancement plants, developed for flower visitors protection in low- and middle-income countries, showed multiple benefits for farmers of pollinator-dependent crops, but potential benefits of FAP for production of pollinator-independent crops have not yet been assessed. Therefore, we conducted in 2021 FAP trials with wheat (Triticum aestivum) as the main crop in two regions of Morocco where cereals are mainly grown in monocultures in field sizes ranging from 2 to 5 ha. We tested the effects of fields adding marketable habitat enhancement plants (MHEP; coriander and canola) versus control fields on pests, natural enemies, flower visitors, and net income. We found significantly lower abundance and diversity of pests in wheat fields using MHEP, but no effect on natural enemy presence or net income. The strips of MHEP attracted a high number of flower visitors in both regions (Settat and Sidi Slimane), they supported flower visitor communities by providing plant resources and alternative habitat in monocultural landscapes extremely degraded for flower visitors.